2020 59th IEEE Conference on Decision and Control (CDC) 2020
DOI: 10.1109/cdc42340.2020.9303761
|View full text |Cite
|
Sign up to set email alerts
|

Equivariant Systems Theory and Observer Design for Second Order Kinematic Systems on Matrix Lie Groups

Abstract: This paper presents the equivariant systems theory and observer design for second order kinematic systems on matrix Lie groups. The state of a second order kinematic system on a matrix Lie group is naturally posed on the tangent bundle of the group with the inputs lying in the tangent of the tangent bundle known as the double tangent bundle. We provide a simple parameterization of both the tangent bundle state space and the input space (the fiber space of the double tangent bundle) and then introduce a semi-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The practical applicability of this approach, named "Imperfect-IEKF" by Barrau [5], has been confirmed by several authors [5], [6], [7]. Recent work [8] on second order systems on Lie-groups has demonstrated that there is a natural symmetry that can be used to model both configuration and velocity states in a single geometry. This symmetry draws from advances in the field of equivariant system theory and observer design [9], [10], [8], [11] and provides a framework for stochastic filter design that applies to a broader class of systems than the IEKF while specialising back to the IEKF for groupaffine systems on Lie-groups [12].…”
Section: Introduction and Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…The practical applicability of this approach, named "Imperfect-IEKF" by Barrau [5], has been confirmed by several authors [5], [6], [7]. Recent work [8] on second order systems on Lie-groups has demonstrated that there is a natural symmetry that can be used to model both configuration and velocity states in a single geometry. This symmetry draws from advances in the field of equivariant system theory and observer design [9], [10], [8], [11] and provides a framework for stochastic filter design that applies to a broader class of systems than the IEKF while specialising back to the IEKF for groupaffine systems on Lie-groups [12].…”
Section: Introduction and Related Workmentioning
confidence: 93%
“…Recent work [8] on second order systems on Lie-groups has demonstrated that there is a natural symmetry that can be used to model both configuration and velocity states in a single geometry. This symmetry draws from advances in the field of equivariant system theory and observer design [9], [10], [8], [11] and provides a framework for stochastic filter design that applies to a broader class of systems than the IEKF while specialising back to the IEKF for groupaffine systems on Lie-groups [12]. In [13], a new symmetry was introduced to couple the navigation state as well as the accelerometer and gyroscope biases in a single geometric structure.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…The gauge invariance inherent in the SLAM problem induces a homogeneous space structure that underlies recent work by the authors [vHM20,vMHT20,vMHT19,vM21]. This perspective is critically important for the visual SLAM problem where cameras are the primary exteroceptive sensor and the SLAM problem can no longer be modelled [vGHM20] using the SE n+1 (3) geometry introduced by Barrau et [NvMH19,NvHM20] for second order kinematics, while Phogat et al considered a direct product structure for general second order systems on Matrix Lie groups [PC20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is promising to embed the inertial-integrated navigation system into an equivariant system so that an equivariant filter can be designed as a kinematic system on a Lie group. Equivariant system theory has been used for the full second order kinematic systems on TSO(3) (Ng et al 2019) and TSE(3) (Ng et al 2020), where the second order means both the first and second derivatives of position are considered in the kinematic system.…”
Section: Introductionmentioning
confidence: 99%